Do passado ao presente do PCPA : as violações de direitos humanos na execução penal e o papel da OEA - Cappellari, Mariana Py Muniz (2013)
This dissertation, linked to the area of concentration Penal System and Violence, line - Criminal Legal Systems Research Contemporary, had the intention to approach the structuring of the PCPA, his past to his present, to pay attention to the human rights violations that then comes to criminal enforcement, as well as seeking to identify what is the role of the OAS in this context, given representation, with specific with PCPA, addressed to the Inter- American System of Human Rights Protection . Thus, at first we demonstrate how it originated the PCPA, which were their purposes, the intended recipient, and stood structured, even before the lack of jobs versus prison population, until we get to your current situation. Subsequently, we discus about the problems generated in the criminal enforcement on the repeated violation of Human Rights. Therefore, it proved necessary to address the state of the art Human Rights in Constitutional sphere. Traced, then the conceptualization between Human Rights and Fundamental Rights, entering itself in some constitutional principles applicable to criminal enforcement, which proved to be of paramount importance, because while the object contrast, allowed to verify in a timely species of human rights violations originated, such as overcrowding, loss of internal control and dominion of PCPA factions; precariousness of health care, material assistance withheld; absence of conditions of work , study, and other instruments of rehabilitation; supply conditions; magazine and conjugal visits, in addition to the damage to so-called benefits enforceable. We conclude, at this point, the confirmation of human rights violations, as well as the ineffectiveness of the law as a response. Thus, we then develop some considerations about the representation sent to the CIHR: If PCPA and structuring of the Inter-American Human Rights System, in order to raise the possible routes to be followed by representation through the analysis of the ACHR, in its role assertion of rights as well as on its incorporation into domestic constitutionalism. Still, we see the process, the roles and responsibilities of the Commission and the Court, the alleged representation, even bringing into play specific jurisprudence on the matter. Finally, we present the advances possible even if not accepted the representation in terms of visibility of a reality so important, considering, at this point, the need for a flexible concept of sovereignty, as well as posture and will state when it comes to compliance with decisions issued by International Systems of Human Rights Protection. Finally, we conclude that given the existence of a substantial body of legislation on the matter, based on the national or international law, as well as confirmed the human rights violations based on criminal enforcement, and even considering the lack of coercion by higher part of the Inter-American System of Human Rights Protection, regarding the compliance with its decisions, urges a shift in the construction of the mindset of the actors and operators of the penal system, given that it is only through them that the system operates, and which may pursue a criminal enforcement fairer and more human.